Species of Garra (Cyprinidae: Labeoninae) in the Salween River basin with description of an enigmatic new species from the Ataran River drainage of Thailand and Myanmar - Tangjitjaroen, Weerapongse; Randall, Zachary S.; Tongnunui, Sampan; Boyd, David A.; Page, Lawrence M. (Zootaxa, 2023)
Garra panitvongi, new species, is described from the Ataran River drainage, Salween River basin, of southeastern Myanmar and western Thailand. It is the sixth species of Garra known from the Salween River basin and is readily distinguished from all congeners by the red-orange color of the body and caudal fin, and a pointed proboscis with a blue stripe on each side from the anterior margin of the orbit to the tip of the proboscis and with the stripes forming a V-shape. Garra panitvongi is known in the aquarium trade as the Redtail Garra. Descriptive information is provided on poorly known species of Garra in the Salween River basin, and Garra nujiangensis is transferred to Ageneiogarra.